Scale Construction of Self-Assessment of Entrepeneurial Competencies - Benedicta Prihatin Dwi Riyanti; Christiany Suwartono (Journal of International Conference Proceedings (JICP), 2018)
Entering the ASEAN economic community today, Indonesia needs to develop the number of entrepreneurs, primarily comes from student graduate of the vocational high school. The curriculum on vocational education in Indonesia consists of entrepreneur subjects that developed the students with technical competence (hard skills) and non-technical competencies (soft skills). In this study, the authors construct a measure of entrepreneurial competencies consists of soft skill competence and hard skill competence. Participants were asked to assess own abilities in various competencies, according to the statements provided. The participants were 258 graduated vocational students from Yogyakarta and Jakarta. Researchers made 137 initial statement and in the end, took 24 best statement. Results of the reliability and validity of the questionnaire were satisfactory. Future studies are needed to test the predictive power of the test tool to the success of students in entrepreneurship. Keywords: competencies, entrepreneurship, scale construction, selfassessment, vocational school.